NON-IDEAL SYSTEM WITH QUADRATIC NONLINEARITIES CONTAINING A TWO TO-ONE INTERNAL RESONANCE - Rocha, Rodrigo T. [UNESP]; Balthazar, Jose M. [UNESP]; Quinn, D. Dane; Tusset, Angelo M.; Felix, Jorge L. P.; ASME (Amer Soc Mechanical Engineers, 2016)
The dynamical behaviour of a non-ideal three-degrees-of freedom weakly coupled system associated with the quadratic nonlinearities in the equations of motion is investigated. The main system consists of two nonlinear mechanical oscillators coupling with quadratic nonlinearities and in which possess a 2:1 internal resonance between their translational movements. Under these conditions, we analyzed the response when a DC unbalanced motor with limited power supply (non-ideal system) excites the main system. When the excitation frequency is near to second natural frequency of the main system, saturation and jump phenomena are presented. Then, this work will analyze some torques of the motor, which causes the phenomena, and due to high amplitudes of motion will be possible to look for a way to harvest energy in a future work.